Analisis Kasus Bank Jago: Eks Karyawan Bobol 112 Rekening Nasabah Senilai Rp1,39 Miliar melalui Pembukaan Blokir Ilegal - Faza Fatkhun Nadhif; Muhammad Rizki Meidianto; Yusuf Suprayogi; Mahesya Ayu Rahman; William Putra Hatorangan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The case of the burglary of 112 Bank Jago customer accounts by a former employee with losses reaching IDR 1.39 billion reflects a serious threat to the security of the digital banking system. The mode of crime in the form of illegally opening blocking of accounts by perpetrators who have special access indicates weaknesses in internal supervision and system security. This research aims to identify weak factors in Bank Jago's security system, the role of law enforcement officers (APH) in handling this case, as well as the legal implications for the bank's responsibilities. The approach used is a qualitative method with descriptive analysis of secondary data, including banking regulations, case reports and related publications. The analysis results show that the main weaknesses lie in the lack of internal supervision, unlimited system access, a vulnerable security system, and suboptimal authentication and activity monitoring mechanisms. APH's role has proven to be crucial in detecting and handling cases, including making arrests, confiscating evidence, and preparing legal cases. This case provides important lessons for the banking industry to strengthen security policies, including implementing multi-factor authentication, monitoring log activity, and regular audits. In addition, cooperation between banks and legal authorities must be improved to mitigate similar risks in the future. This strategy not only aims to protect customers but also restore public trust in digital banking services.